Concurrent Panniculectomy With Abdominal Wall Reconstruction: A Propensity-scored Matched Study of Quality Improvement Outcomes - Alexis M. Holland, MD; William R. Lorenz, MD; Matthew N. Marturano, MD; Rose K. Hollingsworth, BA; Gregory T. Scarola, MS; Brittany S. Mead, MD; B. Todd Heniford, MD; Vedra A. Augenstein, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Concurrent panniculectomy with abdominal wall reconstruction (CP-AWR) as a single-stage operation has reported increased complications, but constant quality improvement can improve results. This study describes outcomes for 21 years, impacted by evidence-based-practice changes. Methods:. Prospectively maintained database was reviewed for CP-AWR and separated by surgery date: “early” (2002–2016) and “recent” (2017–2023). A 1:1 propensity-scored matching was performed based on age, tobacco use, body mass index (BMI), American Society of Anesthesiologists (ASA) score, wound class, and defect size. Results:. Of 701 CP-AWRs, 196 pairs matched. Match criteria were not significantly different between early and recent groups, except for BMI (34.6 ± 7.2 versus 32.1 ± 6.01 kg/m2; P = 0.001). Groups were comparable in sex and diabetes, but recent patients had fewer recurrent hernias (71.4% versus 56.1%; P = 0.002). Recent patients had more biologic (21.9% versus 49.0%; P < 0.001) and preperitoneal mesh (87.2% versus 97.4%; P = 0.005). Readmission and reoperation did not significantly differ, but length of stay (8.3 ± 6.7 versus 6.5 ± 3.4 d; P = 0.001) and wound complications decreased over time (50.5% versus 25.0%; P < 0.001). Hernia recurrence rates improved (6.6% versus 1.5%; P = 0.019), but follow-up was shorter (50.9 ± 52.8 versus 22.9 ± 22.6 months; P < 0.0001). Conclusions:. Despite patient complexity, outcomes of CP-AWR improved with implementation of evidence-based-practice changes in preoperative optimization, intraoperative technique, and postoperative care. This large dataset demonstrates the safety of a single-stage repair that should be part of hernia surgeons' repertoire.